2015
DOI: 10.1039/c5ta03164h
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional architecture of carbon wrapped multilayer Na3V2O2(PO4)2F nanocubes embedded in graphene for improved sodium ion batteries

Abstract: A novel Na3V2O2(PO4)2F@carbon/graphene three dimensional (3D)architecture (NVPF@C/G) is developed through a simple approach for the first time, which demonstrates superior sodiation properties for Na-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 55 publications
2
80
0
Order By: Relevance
“…3f) shows two characteristic peaks with binding energy of 516.7 eV (V 2p 3/2 ) and 523.8 eV (V 2p 1/2 ), indicating the existence of V 4+ species in NVPF@C samples. This is consistent with previous reports [21,33]. Moreover, the highresolution of C 1s spectrum in Fig.…”
Section: Resultssupporting
confidence: 93%
“…3f) shows two characteristic peaks with binding energy of 516.7 eV (V 2p 3/2 ) and 523.8 eV (V 2p 1/2 ), indicating the existence of V 4+ species in NVPF@C samples. This is consistent with previous reports [21,33]. Moreover, the highresolution of C 1s spectrum in Fig.…”
Section: Resultssupporting
confidence: 93%
“…These unit cell parameters were typical of Na 3 V 2 O 2 (PO 4 ) 2 F with the NASICON-type structure. 6,13,16,26,27 Nevertheless, other studies have reported the primitive a P ¼ a I O2, c P ¼ c I tetragonal supercell for Na 3 5,12,15 and a more systematic crystallographic investigation revealed that the primitive supercell was indeed stable at room temperature, while the smaller I-centered tetragonal subcell was characteristic of the high-temperature polymorph of Na 3 V 2 O 2 (PO 4 ) 2 F (stable above $500 K). 28 To verify the unit cell of the Na 3 V 2 O 2 (PO 4 ) 2 F phase prepared by the MW-HT method, we performed electron diffraction analysis.…”
Section: Synthesis and Crystal Structuresmentioning
confidence: 94%
“…For example, using Na 2 HPO 4 as a phosphorus source results in the formation of nanoowers with a diameter of 8 mm and thickness of 4 mm, while using NH 4 H 2 PO 4 leads to a cube-like morphology and particles with sizes less than 1 mm. 14,27 However, treatment time is a limiting parameter of hydrothermal synthesis, with up to 60 h perhaps required to afford the nal product. 13 The long synthesis duration is closely related with the requirement to heat the solution homogeneously, while heating occurs from the "outside" to "inside".…”
Section: Synthesis and Crystal Structuresmentioning
confidence: 99%
“…As can be seen from Figure 3A, peaks at 517.5 eV and 524.6 eV are attributed to the V 2p 3/2 and V 2p 1/2 , indicating trivalent vanadium in NVPF@C‐4 is successfully reduced from V 2 O 5 . Also, the C 1s peak at 284.5 eV in NVPF@C‐4 (Figure 3B) are fitted to four peaks at 284.6 eV, 285.5 eV, 286.6 eV and 288.9 eV, which are assigned to the C=C, C−C, C−N and O−C=O bonds, respectively 18,23 . The absorption peak at 400.9 eV is belonging to N 1s, which is originated from the decomposition of CTAB.…”
Section: Resultsmentioning
confidence: 92%
“…Like most polyanion cathode materials, Na 3 V 2 (PO 4 ) 2 F 3 also suffers from poor electronic conductivity (10 −12 S·cm −1 ) because tetrahedron [PO 4 ] separates vanadium atoms. In order to improve the electrochemical performance of Na 3 V 2 (PO 4 ) 2 F 3 , controlling the particle size, carbon coating, and metallic ion doping are three major means 16‐18 …”
Section: Introductionmentioning
confidence: 99%